Crack propagation simulation of fiber-reinforced composite laminates based on non-ordinary state-based peridynamics - Ji Zhou; Songrong Qian (Materials Research Express)
Peridynamics theory has become a popular approach for analyzing fracture damage in fiber-reinforced composite laminates because it uses integral equations to describe the mechanical behavior among internal material points. However, simulating fracture damage with bond-based peridynamics is challenging when incompressible components are present. To address this issue, this paper proposes an improved model based on non-ordinary state-based peridynamics theory. In this model, tensor forms are used to describe the interactions between material points in fiber-reinforced composites, and the Hoffman strength criterion is introduced to capture the different responses under tensile and compressive loading. Moreover, the OpenMP approach is employed to accelerate the simulation process. The model is validated through a displacement load simulation on a composite laminate under displacement load, and the displacement results agreed well with those obtained from the finite element method, with a displacement error at the midline of 0.73%. Additionally, analyses of composite laminates with defects and real material tensile experiments further verify the detailed processes of damage initiation, propagation, and crack growth. The proposed method provides a mesh-free, efficient tool for dynamic fracture analysis in composite materials, with significant potential for applications in aerospace and marine engineering.